Selective down-regulation of tyrosinase family gene TYRP1 by inhibition of the activity of melanocyte transcription factor, MITF - Fang, Dong (Oxford University Press, 2002)
Tyrosinase (TYR), tyrosinase-related protein-1 (TYRP1/gp75) and dopachrome tautomerase (DCT/TYRP2) belong to a family of melanocyte-specific gene products involved in melanin pigmentation. During melanocyte development expression of tyrosinase family genes is thought to be orchestrated in part by the binding of a shared basic helix–loop–helix transcription factor MITF to the M box, a regulatory element conserved among these genes. In transformed melanocytes, expression of tyrosinase and TYRPs is highly variable. Whereas TYR expression in melanoma cells is regulated by both transcriptional and post-translational mechanisms, TYRP1/gp75 transcription is often completely extinguished during melanoma tumor progression. In this study, we investigated the mechanisms of selective repression of TYRP1 transcription. Interestingly, in early stage melanoma cells TYRP1 mRNA could be induced by inhibition of protein synthesis. Transient transfection experiments with a minimal TYRP1 promoter showed that the promoter activity correlates with expression of the endogenous TYRP1 gene. Nucleotide deletion analysis revealed novel regulatory sequences that attenuate the M box-dependent MITF activity, but which are not involved in the repression of TYRP1. Gel mobility shift analysis showed that binding of the transcription factor MITF to the TYRP1 M box is selectively inhibited in TYRP1(–) cells. These data suggest that protein factors that modulate the activity of MITF in melanoma cells repress TYRP1 and presumably other MITF target genes.